Understanding Why Clinicians Answer or Ignore Clinical Decision Support Prompts - Carroll, A.E.; Anand, V.; Downs, S. M. (Applied Clinical Informatics, 2012)
Introduction: The identification of key factors influencing responses to prompts and reminders within a computer decision support system (CDSS) has not been widely studied. The aim of this study was to evaluate why clinicians routinely answer certain prompts while others are ignored. Methods: We utilized data collected from a CDSS developed by our research group – the Child Health Improvement through Computer Automation (CHICA) system. The main outcome of interest was whether a clinician responded to a prompt.Results: This study found that, as expected, some clinics and physicians were more likely to address prompts than others. However, we also found clinicians are more likely to address prompts for younger patients and when the prompts address more serious issues. The most striking finding was that the position of a prompt was a significant predictor of the likelihood of the prompt being addressed, even after controlling for other factors. Prompts at the top of the page were significantly more likely to be answered than the ones on the bottom.Conclusions: This study detailed a number of factors that are associated with physicians following clinical decision support prompts. This information could be instrumental in designing better interventions and more successful clinical decision support systems in the future.
Keywords: Clinical decision support systems; CHICA; screening; prompts; EMR